Hard LRE Choices in the Era of Inclusion: Rights and Their Implications. (June 2023) - Kauffman, James M.; Burke, Mack D.; Anastasiou, Dimitris
Rights of students are often misunderstood. Civil rights of minorities granted by the U.S. Supreme Court are confused with human rights of individuals with disabilities granted by the U.S. Congress. Federal law applying to the education of individuals with disabilities requires that difficult decisions be made by families and schools regarding how to address four different and interrelated provisions of Public Law 94-142 of 1975 (now the Individuals with Disabilities Education Improvement Act of 2004 or IDEA): (a) a free, appropriate public education (FAPE), (b) an Individualized Education Program (IEP), (c) placement in the least restrictive environment (LRE), and (d) a full continuum of alternative placements (CAP). Special attention is given to LRE because the full inclusion movement and other influences related to a portion of disability studies have made it the central issue in special education. Under the law, three hard-to-answer questions must be asked in all cases involving special education: (a) What is an appropriate special education for a particular student with a disability? (b) What is the LRE in which that most appropriate education can occur for that individual student? (c) What is the CAP related to that individualized appropriate education?